On opinion - Martínez, Luciana (Con-Textos Kantianos. International Journal of Philosophy, 2024)
Kant analyses the notion of opinion within the framework of his explanation of what it means to hold a judgement to be true. To give an opinion is to consider something to be true, without objective or subjective grounds for doing so. Despite being unfounded and thus epistemically unlegitimised, opinions can be valuable as part of the process of knowing. This article discusses the concept of opinion, explains what value opinions have, and discusses why freedom of thought is important for that value.